2016
DOI: 10.1016/j.jallcom.2016.01.217
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of epitaxial LiFe5O8 thin films grown by chemical vapor deposition

Abstract: a b s t r a c tWe report on detailed microstructural and atomic ordering characterization by transmission electron microscopy in epitaxial LiFe 5 O 8 (LFO) thin films grown by chemical vapor deposition (CVD) on MgO (001) substrates. The experimental results of LFO thin films are compared with those for bulk LFO single crystal. Electron diffraction studies indicate weak long-range ordering in LFO (a-phase) thin films in comparison to bulk crystal where strong ordering is observed in optimally annealed samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Irradiation can induce antisite defects (LnormaliFnormaleOct, LnormaliFnormaleTetra and FnormaleLi), which redistributes cations in the A‐ and B‐sites, so the order‐disorder transformation of LFO can be accomplished by electron beam irradiation. [ 16 ] An Fe Oct atom has a smaller TDE than an Fe Tetra atom, so Fe vacancies at octahedral sites (B sites) are larger than those at tetrahedral sites (A sites). Thus, irradiation leads to a decrease in magnetization, which has been observed in LFO undergoing proton irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation can induce antisite defects (LnormaliFnormaleOct, LnormaliFnormaleTetra and FnormaleLi), which redistributes cations in the A‐ and B‐sites, so the order‐disorder transformation of LFO can be accomplished by electron beam irradiation. [ 16 ] An Fe Oct atom has a smaller TDE than an Fe Tetra atom, so Fe vacancies at octahedral sites (B sites) are larger than those at tetrahedral sites (A sites). Thus, irradiation leads to a decrease in magnetization, which has been observed in LFO undergoing proton irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation can lead to the creation of a wide variety of defects, such as point defects, phase changes, and clusters of defects, which modify local atomic configurations, thus affecting the magnetic properties of LFO. Various forms of irradiation, such as γ‐ray, [ 13–15 ] electron, [ 16 ] swift heavy ion, [ 17 ] proton, [ 18 ] and laser irradiation, [ 19,20 ] have been reported in the literature. Loukya et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cycling performance is much better than that of the reported pure phase α-LiFeO 2 [ 16 , 23 , 24 ]. The capacity decreased as the temperatures increase, which might be attributed to the higher sintering temperature leading to the impurity phase of LiFe 5 O 8 , which is considered responsible for the sharp decrease of initial discharge capacity [ 25 , 26 ]. Furthermore, Sakurai found that α-LiFeO 2 synthesized at high temperature was electrochemically inactive, as the higher temperature may increase the disorder degree of iron ions on lithium sites and block lithium diffusion pathways [ 8 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%